Interval elimination method for stochastic spanning tree problem - Mohd, Ismail (1994)
The optimum spanning tree problem has been well considered and until now several powerful algorithms have been proposed. This problem has been generalized toward a stochastic spanning tree problem in which edge weights are not constant but random variables. A method called an interval elimination is used for solving the stochastic spanning tree problem which has been transformed into its proxy deterministic equivalent problem. © 1994.